The policy narrative of the outsourcing system in Indonesia - Alamsyah, Alamsyah; Alfani, Hendra; Saraswati, Erlisa; Kusumawati, Novita Sri (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2025)
Law No. 6/2023, which ratifies Government Regulation in Lieu of Law No. 2/2022 on Job Creation, defines outsourcing as the delegation of part of work implementation to other companies through a written outsourcing agreement. This study aims to analyze the narrative structure of Indonesia’s outsourcing policy using the Narrative Policy Framework (NPF), focusing on key elements such as characters (heroes, villains, and victims), setting, plot, and moral of the story. A total of 132 news articles were randomly selected using the keyword “outsourcing” from online sources between November 2, 2020, and December 31, 2023. The data were analyzed using the Discourse Network Analysis (DNA) application. The resulting narrative portrays both workers and outsourcing companies as victims, while the government, outsourcing companies, and service user companies appear both as villains and heroes. The setting includes various regions in Indonesia and covers aspects of job creation and enhancement, workers’ income and welfare, internal company policies, and human resource management. The narrative plot highlights employment policies, associated challenges, and governance of labor regulations. The moral of the story emphasizes the need for effective labor regulations, strict enforcement of employment policies and laws, ongoing policy evaluation, and robust worker protection mechanisms. To foster synergy among stakeholders in shaping effective policies, the government must ensure clear communication of fair and accountable outsourcing principles and design a robust enforcement strategy to address systemic outsourcing issues.